(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
The present article addresses the discussion regarding the recognition of the dependence of the minor under custody for social security purposes, with the scope of considering the right to the death pension benefit and/or imprisonment aid related to his/her guardian insured by Social Security. To this end, in addition to the legislative and doctrinal analysis, recent precedents of the STJ and STF on the matter will be examined, under the focus of EC No. 103/2019.